2022
DOI: 10.1002/glia.24133
|View full text |Cite|
|
Sign up to set email alerts
|

Sex‐specific transcriptome of spinal microglia in neuropathic pain due to peripheral nerve injury

Abstract: Neuropathic pain is a prevalent and debilitating chronic disease that is characterized by activation in glial cells in various pain-related regions within the central nervous system. Recent studies have suggested a sexually dimorphic role of microglia in the maintenance of neuropathic pain in rodents. Here, we utilized RNA sequencing analysis and in vitro primary cultures of microglia to identify whether there is a common neuropathic microglial signature and characterize the sex differences in microglia in pai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 83 publications
0
26
0
Order By: Relevance
“…IFN-γ can also damage the CNS through microglia activation. In addition to activating resting microglia, stimulating the IFN-γR signaling pathway also upregulates the tyrosine kinase Lyn and purinergic P2X4 receptors of microglia, leading to abnormal neuronal excitation in dorsal horn neurons and neuropathic pain ( 45 ).…”
Section: Membrane Receptors and Pathways In Microglia Activationmentioning
confidence: 99%
“…IFN-γ can also damage the CNS through microglia activation. In addition to activating resting microglia, stimulating the IFN-γR signaling pathway also upregulates the tyrosine kinase Lyn and purinergic P2X4 receptors of microglia, leading to abnormal neuronal excitation in dorsal horn neurons and neuropathic pain ( 45 ).…”
Section: Membrane Receptors and Pathways In Microglia Activationmentioning
confidence: 99%
“…Microglia are frequently mixed, exhibiting both phenotypes. The idea of physiological state heterogeneity ( Li et al, 2019 ; Cadiz et al, 2022 ), and gender differences ( Fiore et al, 2022 ; Tansley et al, 2022 ; Ugidos et al, 2022 ) has slowly emerged in recent years, creating a new foundation for our complete understanding of microglia. At the same time, single-cell sequencing technology has also opened a new door for this ( Butovsky et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mainly including: 1. Microglial development ( Wurm et al, 2021 ; Iyer et al, 2022 ) and phenotypes in physiological or pathological conditions, also involving microglial heterogeneity in spatial and temporal ( Masuda et al, 2019 ), gender ( Dockman et al, 2022 ; Fiore et al, 2022 ), or other dimensions. 2.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical pain hypersensitivity test was conducted on the rats of both groups using von Frey fibres [3] at the D0, D3, and D7 timepoints after BND surgery. The rats were acclimated to the testing apparatus for at least 30 min before behavioural testing.…”
Section: Mechanical Pain Hypersensitivity Testmentioning
confidence: 99%
“…Microglia are immune cells that constantly maintain the microenvironment and homeostasis of the central nervous system (CNS) [2][3][4]. Several studies have confirmed the crucial role of microglia in neuropathic pain [3,4].…”
Section: Introductionmentioning
confidence: 99%